Evaluation of anti-phenolic glycolipid-I IgM and CD4/CD8 T cell subsets value as high risk determination indicator for individuals residing in a leprosy endemic area in Indonesia (Faculty of Medicine Universitas Indonesia, 1999)
[no abstract available]